Efforts To Improve Science Learning Outcomes On Economic Activity Materials Through Modelscontextual Teaching And Learning (CTL) Students Class IVSD State 064017 Medan - Nanda Ayu Setiawati, Taruli Marito Silalahi, Winny Sunfriska Limbong, Febriani Saree Door (Pusdikra-Publishing.com, 2022)
This study aims to improve social studies learning outcomes by using a Contextual Teaching and Learning (CTL) model in fourth grade students of SD Negeri 064017 Medan. This type of research is classroom action research (Clasroom Action Research). The research subjects in this research were all grade IV students of SD Negeri 064017 Medan Perjuangan totaling 31 students. This research model uses the Kemmis and Mc Taggart models. The method used in this research is 1) test, 2) observation, 3) documentation. The technique used to analyze data is qualitative data and quantitative data. Social studies learning by using the Contextual Teaching and Learning (CTL) model can improve social studies learning outcomes for fourth grade students of SD Negeri 064017 Medan. Increased social studies learning outcomes in the first cycle by an average of 66.45 and an increase in the second cycle by 81.9